Analysis of skin pigmentation - Hani, A.F.M. (CRC Press, 2014)
Vitiligo is a pigmentary skin disorder resulting from abnormal melanin production. This is due to the destruction of epidermal melanocytes. Physically, vitiligo lesion areas appear as paler skin tone compared with the surrounding skin or they may be completely white 1. Figure 5.1 shows a patient with vitiligo lesions. The prevalence of vitiligo worldwide varies, ranging from 0.1% to 2%. The prevalence of vitiligo is not related to any skin types, sex, or socioeconomic status 2. Vitiligo is unpredictable and may remain stable for years before worsening. The disease is most disfiguring in dark-skinned racial and ethnic groups where the contrast between the depigmented and healthy skin is more noticeable. It has been reported that patients with vitiligo have an increased risk of autoimmune diseases such as thyroid disease (Hashimotoâs thyroiditis and Graveâs disease) and Addisonâs disease 2, 3. Â© 2014 by Taylor & Francis Group, LLC.